Healthy Lakes and Vibrant Economies: Linking History, Sense of Place, and Watershed Protection in the Belgrade Lakes Region - Fleming, James; Love, Erin (Maine Policy Review, 2012)
Using interviews, targeted questionnaires, and historical documents, James Fleming and Erin Love show how history and “sense of place” can help encourage individuals to support environmental protection. The project they describe focuses on watershed protection in the Belgrade Lakes region of Maine, and is part of a larger Sustainability Solutions Initiative project in that region. They argue that “connection to place leads to caring about it.”
Keywords: Maine; watershed protection; sense of place